Clinical attachments: fond farewell or new beginning? A survey of the attitudes and practice of medical consultants and international medical graduates. Issue 977 (7th March 2007) - Wawdhane, Sudhir; Saraf, Vivek; Davidson, Sharon; Trewby, Peter
Abstract : Objectives: To analyse the experience of clinical attachment (CA) of international medical graduates (IMGs) and consultants. Design: Analysis of questionnaires and CVs. Setting and participants: 573 IMGs applying for a house officer post and 102 consultant physicians working in North East England. Results: IMGs had spent a mean of 16 months unemployed, of which 3.8 months was spent on CAs. The median number of CAs was two and the average number of applications sent before obtaining a CA was 73. 90% of IMGs found their CA helpful and 57% would not take up a post without a CA first. Criticisms related to lack of responsibility, isolation and poor job prospects. 90% would apply for honorary posts if advertised. 73% had received induction at the onset of placement, but only 32% had been assessed at the end. 50% of consultants took CAs and only 4% were thinking of stopping doing so. Those without CAs blamed work pressure (43%) and pressure from their employer (23%). Conclusions: There are deficiencies in pastoral care, the application process and assessment, but CAs are valued by IMGs and offered by half the consultants surveyed. New immigration rules will mean fewer IMGs will come to the UK, but CAs will be needed by those that do, as well by refugees and European Economic Area (EEA) graduates. The tradition of CAs for international graduates could be used to accommodate those coming to the UK on exchanges and scholarships and form part of the recently announced Medical Training Initiative for IMGs.